2015
DOI: 10.1021/jacs.5b05351
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Reversible Translation Control Using γPNA Probes

Abstract: On-demand regulation of gene expression in living cells is a central goal of chemical biology and antisense therapeutic development. While significant advances have allowed regulatory modulation through inserted genetic elements, on-demand control of the expression/translation state of a given native gene by complementary sequence interactions remains a technical challenge. Toward this objective, we demonstrate the reversible suppression of a luciferase gene in cell-free translation using Watson-Crick base pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…For example, a similar strategy could be applied in the field of synthetic biology to design genetic circuits that, through different modulators, can finely control biological pathways and cellular functions including transcription and gene expression. [30][31][32][33][34][35][36][37][58][59] …”
Section: Discussionmentioning
confidence: 99%
“…For example, a similar strategy could be applied in the field of synthetic biology to design genetic circuits that, through different modulators, can finely control biological pathways and cellular functions including transcription and gene expression. [30][31][32][33][34][35][36][37][58][59] …”
Section: Discussionmentioning
confidence: 99%
“…In addition, GPNA was less cytotoxic compared with PNA-polyarginine conjugates. In a recent study, Bruchez et al demonstrated the reversible suppression of a luciferase gene using a γ-modified PNA (γPNA) sequence and a non-complementary toehold [ 91 ]. The antisense γPNA strand could be removed by a second, fully complementary γPNA strand via a strand displacement reaction, leading to the continuation of translation.…”
Section: Chemically Modified Nucleic Acid Analoguesmentioning
confidence: 99%
“…While significant advances have been made toward the regulation of gene expression by manipulation of genetic elements, on demand control of transcription/translation of a desired gene with sequence specificity remains a challenge. [ 40 ] As a step toward this goal, Canady et al . demonstrated the reversible suppression of a luciferase gene in cell‐free translation, by targeting a mRNA transcript using a complementary γPNA sequence with a non‐complementary toehold.…”
Section: Pna In Regulating Gene Expressionmentioning
confidence: 99%
“…Furthermore, the authors showed that instead of γPNA, complementary RNA can also displace the bound antisense γPNA, presenting possibilities of regulation involving the native cellular gene expression pathways. [ 40 ] If developed to be applicable within in vitro and in vivo settings, such a tool would be very useful in the field of modulating gene expression.…”
Section: Pna In Regulating Gene Expressionmentioning
confidence: 99%